E se Osea non fosse esistito davvero…? - Zawadzki, Arnold (The Biblical Annals, 2020)
The article presents an extended review of James M. Bos’s book Reconsidering the Date and the Provenance of the Book of Hosea. The Case for the Persian-Period Yehud, against the backdrop of the issue of the new historicism in biblical studies. After a brief overview of the phenomenon of this new historicism (its genesis and historical development), Bos’s approach is discussed from the point of view of its ideological-philosophical context. Then a detailed analysis of the entire structure of Bos’s book is presented, along with a critical assessment of his reasoning. The author of the article argues that the new historicist approach is completely subjective and wrong, as it absolutizes a philosophical principle without admitting the element of faith or any possibility of coincidence or doubt.